2008
DOI: 10.1136/bjo.2007.129858
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the quinolone resistance determining region in Staphylococcus epidermidis recovered from conjunctiva and their association with susceptibility to various fluoroquinolones

Abstract: Background:Staphylococcus epidermidis is one of the prominent pathogens in ocular infection. The prevalence of mutations in the quinolone resistance determining region (QRDR) area in S epidermidis isolated from the ocular surface and its association with fluoroquinolone resistance has not been fully elucidated.Methods:Mutations in the QRDR of gyrA, gyrB, parC, and parE genes of 138 isolates of S epidermidis recovered from the human conjunctival flora were analysed. The minimal inhibitory concentrations (MICs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 19 publications
9
43
1
Order By: Relevance
“…Low-level resistance isolates demonstrated only a single point mutation (Ser84Phe) in gyrA, whereas isolates carrying a second point mutation (Ser84Phe and Glu88Lys) showed high-level resistance. Previous work has also shown that the additional substitution at codon 88 from a glutamic acid to lysine in the gyrA of S. epidermidis ocular isolates is related to a higher MIC of 8-methoxyfluoroquinolones (18,19). Although overexpression of the efflux pump might play a role in the high-level fluoroquinolone resistance, our present and previous data suggest that the level of resistance for 8-methoxyfluoroquinolones increases as additional mutations are included in the QRDR of gyrA (28,29).…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Low-level resistance isolates demonstrated only a single point mutation (Ser84Phe) in gyrA, whereas isolates carrying a second point mutation (Ser84Phe and Glu88Lys) showed high-level resistance. Previous work has also shown that the additional substitution at codon 88 from a glutamic acid to lysine in the gyrA of S. epidermidis ocular isolates is related to a higher MIC of 8-methoxyfluoroquinolones (18,19). Although overexpression of the efflux pump might play a role in the high-level fluoroquinolone resistance, our present and previous data suggest that the level of resistance for 8-methoxyfluoroquinolones increases as additional mutations are included in the QRDR of gyrA (28,29).…”
Section: Discussioncontrasting
confidence: 44%
“…Fluoroquinolone-resistant CoNS isolates from the normal conjunctiva microbiota have been recovered from patients undergoing intraocular surgery and intravitreal injection (4,5,(22)(23)(24). In addition, two studies found mutations within the QRDR in around 50% to 58% of S. epidermidis isolates from in the conjunctival sacs before preoperative instillation of antibiotic from patients undergoing intraocular surgeries (18,19). Although a double point mutation was found for a few isolates in both studies, 38% to 41.6% of S. epidermidis isolates from conjunctival sacs preoperatively harbored at least one point mutation in the gyrA gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If one of the strains was found to be resistant to LVX and MXF, it was allocated to the QR group, although they were susceptible to the remaining fluoroquinolones. The quinolone resistance-determining regions (QRDRs) of the gyrA, gyrB, parC, and parE genes were amplified by PCR using a set of previously described primers (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%